Manual of research techniques in cardiovascular medicine - Ardehali, Hossein. (editor); Bolli, Roberto. (editor); Losordo, Douglas. (editor); Shah, Sanjiv. (section editor); Bayeva, Marina. (section editor); Rines, Amy. (section editor); Wasserstrom, Andy. ( section editor) (Hoboken Wiley Blackwell, John Wiley & Sons, Ltd., 2014)
Diagnostic Pathology: Infectious Diseases takes a comprehensive look at infectious diseases, their anatomic manifestations, and how to ensure a complete and accurate sign out at the microscope. A user-friendly chapter landscape and thousands of high-quality images combine to make this medical reference book a key companion for the general surgical pathologist or resident in training. Comprehensive discussions on how to sign out cases. Formatted into sections by organism type (Virus, Bacteria, Fungi, and Parasite), and further divided by those that can be diagnosed on histological appearance
Includes bibliographical references and index.
Keywords: Cardiovascular Diseases; Cardiology--methods.; Models, Cardiovascular; Research Design